Corporate Governance and the Time to Full Exit in the Private Equity Divestment Process on Warsaw Stock Exchange - Sosnowski, Tomasz (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
This paper investigates empirically the links between the specific solutions of corporate governance in portfolio companies of private equity funds and the duration of divestment process after the first listing of company’s shares on the stock market. Using a sample of 41 IPOs from Warsaw Stock Exchange between 2005 and 2015 I find that the pre‑IPO set up corporate governance significantly affects the time of the private equity funds’ full exits. I find evidence that the higher share of private equity funds in the total number of votes at the general meeting of the company’s shareholders before the IPO negatively impacts the chance of the full exit occurrence. However, the data reveal that the syndication and previous experience of private equity fund in IPO exits are important factors affecting the probability of the investment’s end.